Experiences of Infertility in British and Pakistani Women: A Cross-Cultural Qualitative Analysis. Issue 2 (1st February 2016) - Batool, Syeda Shahida; de Visser, Richard Oliver
Abstract : The psychosocial impact of infertility is affected by cultural factors. In this cross-cultural qualitative study we explored the experience of infertility among six women living in Pakistan and eight living in the UK. Although infertile women in the UK and Pakistan had many shared experiences related to their own desires for motherhood and the hopes of others, they also faced unique psychosocial challenges shaped by cultural context. Based on our findings, we suggest a need for further resources and networks to support women, particularly women living in cultures that allow women few fulfilling social roles other than motherhood.